Effectiveness of medical ozone injections into the intervertebral disc on relieving lumbosacral pain–a systematic review and meta-analysis - Cao, Donghui; Li, Xusheng; Zhang, Xiao; Tian, Yanrong; Gu, Wenbo; Zhu, Xi; Yuan, Haifeng (Frontiers in Pain Research, 2025)
ObjectiveTo investigate the clinical efficacy of medical ozone injections into the intervertebral disc on relieving lumbosacral pain. through a systematic review and meta-analysis.MethodsA comprehensive literature search was conducted in PubMed, Cochrane Library, and Web of Science for English-language randomized controlled trials (RCTs) published between January 2010 and January 2025. The study was registered in the PROSPERO International Prospective Register of Systematic Reviews (CRD42023417837). Primary clinical outcomes included pain reduction assessed by Visual Analog Scale (VAS) scores and functional improvement assessed by the Oswestry Disability Index (ODI). Statistical analyses were performed using Review Manager 5.4.ResultsEight RCTs involving 1,744 patients were included. Among them, 903 people received medical ozone injections into the intervertebral discs, while 841 people received other forms of treatment. Meta-analysis showed that medical ozone injections significantly reduced VAS scores (mean difference = −2.13, 95% CI: −2.33 to −1.93, p < 0.05) and improved ODI scores (mean difference = −0.79, 95% CI: −0.95 to −0.63, p < 0.05), indicating superior short-term efficacy compared to conventional treatments.ConclusionsOzone injection into the intervertebral discs is an effective non-invasive treatment method, which can effectively relieve pain in the lumbar and sacral regions, especially showing significant effects in the short term. However, Further long-term studies are warranted to evaluate the durability of clinical benefits.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023417837, PROSPERO CRD42023417837.